La Collection François et Ninon Robelin. - Ceysson, Bernard; Bormand, Marc (Saint-Etienne : Musée d'Art Moderne, 1995)
Attersee, Christian Ludwig ; Beuys, Joseph ; Boetti, Alighiero ; Brecht, George ; Broodthaers, Marcel ; Brus, Günter ; Caniaris, Vlassis ; Carter, Tony ; Dietman, Erik ; Filllou, Robert ; Gerz, Jochen ; Jacquet, Alain ; Le Gac, Jean ; Leisgen, Barbara & Michaël ; Pane, Gina ; Phillips, tom ; Polke, Sigmar ; Rainer, Arnulf ; Roth, Dieter ; Rühm, Gerhard ; Vostell, Wol
La Collection François et Ninon Robelin, Musée d'Art Moderne, Saint-Etienne, 22 janvier au 23 avril 1995
boek